Pengaruh Penggunaan Media Smart Application Menggunakan Model Problem Based Learning Terhadap Hasil Belajar Peserta Didik pada Pembelajaran Pendidikan Pancasila Kelas V Gugus II Kecamatan Lengayang - Ramadhani, Dhini; Masniladevi, Masniladevi; Reinita, Reinita; Fitria, Yanti (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the effect of using Smart Application Creator media with the Problem Based Learning model on student learning outcomes in learning Pancasila Education in class V Gugus II Lengayang District. The method used is quantitative research with a quasi-experiment design. The sample was taken using the Probability Sampling technique, consisting of an experimental class (SDN 27 Pasar Kambang Class VB) and a control class (Class VA). Data was collected through objective tests in the form of multiple choice. Hypothesis testing using the Independent Sample T-Test. This t-test was used to compare the average values of the experimental and control groups. The results showed that the mean value of the experimental class was 78.27 with a standard deviation of 17.81, while the mean value of the control class was 73.51 with a standard deviation of 14.15. The t-test shows the t-count of 2.27, which is greater than the t-table, so it can be concluded that there is a significant effect of using Smart Application Creator media with the Problem Based Learning model on student learning outcomes. This finding shows the importance of applying innovative media and learning models to improve learning outcomes in the classroom.